Stakeholder Focus Groups to Inform a Technology-Based Strategy of Preceptor Support - Cynthia A. Blum; Jeanette Kamciyan; Amy Dean (Hindawi Limited, 2012)
While preceptors are a vital link in student nurse practice education, ongoing support beyond an initial orientation is often lacking. It has been reported in the literature that preceptors experience stress related to difficulties in handling preceptee situations. They are frustrated by negative experiences centered on preceptor-identified hallmarks of unsafe practice including the inability to demonstrate knowledge and skills; attitude problems; unprofessional behavior; and poor communication skills. Their unrealized expectations for novices threaten their commitment to their preceptor role. As part of a larger study testing the effectiveness of podcasts as an ongoing method of preceptor support, this paper addresses the developmental stage of the podcasts. A team of academic and acute care nurse educators developed scripts for eventual filming of four podcasts focusing on unsafe practice issues, designed to provide continual support through web-based availability. The use of podcast technology is consistent with the learning styles of digital natives and is a demonstrated and valuable educational resource to review, reinforce, and clarify difficult concepts. These podcasts were informed through preceptor focus groups to address situational and environmental realism for student behaviors and preceptor responses.